English and Scottish Scholars at the Library of Gian Vincenzo Pinelli (1565–1601) - Philo, John-Mark (Renaissance and Reformation / Renaissance et Réforme, 2019)
Throughout the second half of the sixteenth century, the scholar and collector Gian Vincenzo Pinelli (1535–1601) welcomed poets, mathematicians, antiquarians, and astronomers from every corner of Europe to his vast private library in Padua. These scholars left their mark on Pinelli’s collection, annotating his manuscripts, trading texts, and even making contributions of their very own to his library. This article considers the English and Scottish scholars who visited Pinelli’s collection and the works they gifted to Pinelli. These manuscripts, now preserved at the Biblioteca Ambrosiana, Milan, include an impressive breadth of material, ranging from treatises on England’s schism with Rome to verse commemorating the deaths of fellow scholar–poets. Pinelli, it emerges, was not only hosting scholars from England and Scotland, but also gathering reports, discourses, and what was in many cases highly sensitive intelligence on both nations. These manuscripts thus bear witness to the importance of the Italian private library to the transmission of both ideas and physical texts across the Continent, shining new light on a literary culture that was able to cross and transcend national boundaries.